Apoio de gerência de configuração de software ao ARA-GAwCRe - Borges, Simone de Sousa (2008)
Software systems suffer countless modifications during all its life cycle. Software Configuration Management (SCM) is concerned with organizing, controlling and managing the development and evolution of those systems. GAwCRe is a web application generator built based on Software Product Line for the rehabilitation clinics management domain. The generator instantiation is made through a Modelling Language that is based on the pattern language SiGCli. An ad hoc process has been proposed in order to apply the GAwCRe application generator within Arcabouço de Reengenharia Ágil (ARA). The ARA has the purpose of migrating small and medium procedural systems to the OO paradigm. This research presents an approach of SCM along with ARA to support the Processo de Reengenharia Ágil de Sistemas Legados Utilizando Geradores de Aplicações. The proposed approach uses a process, that is based on the standard IEEE 828-2005, to guide the planning of the SCM activities. Three systems were used: version control, changes control and build management. Other systems and tools are foreseen to provide the integration of the work spaces. The proposed approach supports the employ of the Processo Ágil de Reengenharia Utilizando Geradores de Aplicações associated with the ARA, other generators of applications built based in pattern languages also can be used to aid the design and implementation of the resulting system. Two legacy systems were partially reengineered applying the proposed approach.